Pengaruh Kesehatan Mental Ibu terhadap Status Gizi Anak Usia Pra-Sekolah di Kabupaten Polewali Mandar - Syamsidar, Syamsidar; Supratti, Supratti (Mando Care Jurnal, 2025)
The nutritional problems of pre-school children, especially stunting and underweight, are still a public health challenge in Polewali Mandar Regency which has a relatively high prevalence of stunting. So far, stunting reduction interventions have been more focused on physical and biological factors, while the psychosocial factors of mothers as the main caregivers of children have received less attention. This study aims to analyze the influence of maternal mental health on the nutritional status of pre-school children (36–59 months) in Polewali Mandar Regency. This study uses a quantitative design with a cross-sectional approach  and is carried out in the working area of the Stunting Locus Health Center. The sample consisted of 210 mother-child pairs selected using the proportional random sampling technique. Maternal mental health was measured using the Self-Reporting Questionnaire (SRQ-20), while the child's nutritional status was determined based on the indicators of height by age (TB/U) and body weight by age (BB/U) according to WHO standards. Data analysis was carried out descriptively, bivariate using chi-square test, and multivariate using multiple logistic regression. The results showed that the prevalence of maternal mental health disorders was 39.0%, with the proportion of stunting and underweight children  at 24.8% and 21.9%, respectively. Mothers with mental health disorders have a higher risk of having stunted and underweight than mothers without mental disorders. Maternal mental health is an important determinant of the nutritional status of pre-school children so it needs to be integrated into family and community based nutrition intervention and stunting reduction programs.